Penentuan Konsentrasi Susu Skim Terbaik dalam Pengencer Semen Ayam Kampung Berbahan Dasar Ringer Laktat (DETERMINATION OF OPTIMUM SKIM MILK CONCENTRATION IN KAMPUNG CHICKEN’S SEMEN EXTENDER BASED ON LACTATED RINGERS) - Khaeruddin, Khaeruddin; Nurlinda, Andi; Fattah, Abdul Hakim; Armayanti, Andi Kurnia (Jurnal Veteriner, 2020)
The aim of this study was to determine the best concentration of skim milk in maintaining the quality of Kampung chicken’s spermatozoa during storage at 5 oC. Semen was collected from five roosters which used massage method. Furthermore, semen was divided into five tubes as treatment (no extenders, extenders containing 0%, 6%, 9% and 12% skim milk concentrations), the liquid semen was stored at 5 oC. Observations of motility, viability and abnormalities of spermatozoa were carried out at 0, 12, 24, 36, dan 48 hours. The results showed that there was a very significant difference (P <0.01) among the treatment of motility, viability and abnormalities of Kampung chicken spermatozoa after dilution during storage. Storage of spermatozoa in 6% skim milk concentrate for 48 hours was resulted in motility of 49,00±1,30%, viability of 52,13±1,53% and abnormalities of 20,47±0,47%. The use of lactated ringer extenders with a concentration of 6% skim milk can generally maintain sperm quality which was better than other treatments during storage.